Toxicity assessment of reduced-risk (bio)pesticides on non-Apis bees - Barbosa, Wagner Faria (2015)
It has been said that the human beings and nature would be seriously impacted if bees were wiped out from the world. Indeed, bees are crucial organisms for pollination without which the maintenance and conservation of different biomes would be compromised. Such ecological relevance is accompanied by their economic and social importance through the pollination of numerous wild and cultivated plant species, besides of producing of honey, royal jelly, wax and propolis. In recent decades, the concern with the bee pollinator loss has become increasingly real with many reports of bee declines. Substantial efforts have been made to investigate the causes and consequently to conceive mitigation actions against bee decline. A long list of causes of such decline has been recognized including poisoning by pesticides, particularly insecticides, which has been reported as one of the main factors involved. However, the majority of ecotoxicological risk studies have been restricted to a single model species, the honeybee Apis mellifera, despite the importance of a wide variety of bee species throughout the world. Indeed, honeybees are pollinators of irrefutable value, particularly in the Northern Hemisphere where their commercial pollination is intensively used, and therefore, they deserve attention. Furthermore, as a second shortcoming, these studies have been circumscribed to a few compounds such as neonicotinoid insecticides, which may neglect the potential risks of other compounds to bees. The well-regarded reduced-risk insecticides and bioinsecticides have been presented as alternative compounds for crop management with allegedly low toxicity to bee pollinators. However, because the emphasis of regulatory studies on honeybees, and specifically the perception that the natural origin of bioinsecticides determines their low potential risk to beneficial organisms, the perceived safety of such compounds to non-target species, particularly wild pollinator species, is questionable and should be the target of scrutiny. This work comes to light in order to fill some of these gaps in risk assessments exploring, through laboratory studies, the potential impacts of a select group of reduced-risk insecticides and bioinsecticides on native bees, whose ecological and economic importance can even surpass the honey bee A. mellifera. In the first study performed, the contact and ingestion of spinosad showed high toxicity to workers of two stingless bee species, Partamona helleri and Scaptotrigona xanthotrica, which are important pollinators of wild and cultivated plants in the Neotropical America. However, azadirachtin and chlorantraniliprole exhibited low toxicity to these species with around 100% of surviving individuals after the contact or ingestion at their respective field recommended concentration. Both compounds, however, impaired the vertical free-flight activity of these insects. In the second study performed, lethal and sublethal effects of azadirachtin and spinosad were evaluated through contaminated larval diet of the stingless bee Melipona quadrifasciata anthidioides, another important pollinator in the Neotropics. In this study, the larval survival and pupal weight decreased with increasing doses of both compounds. Both azadirachtin and spinosad also produced deformed pupae and adults. In addition, workers that survived the larval exposure to insecticides had their walking activity compromised only by spinosad, not by azadirachtin. Finally, in a third study, the chronic ingestion of azadirachtin impaired the survival and reproduction of microcolonies of the bumblebee Bombus terrestris, an important bee pollinator species prevailing in the Northern Hemisphere, which is extensively used for commercial pollination in greenhouses. Furthermore, in a laboratory bioassay where the bumblebee workers needed to forage, the lethal and sublethal effects on their reproduction were stronger than the bioassay without foraging under the effect of azadirachtin ingestion. Such findings may challenge the safety notion of reduced-risk insecticides and bioinsecticides when non-Apis bee species are used in toxicology studies, which deserve attention. As future perspectives, we recommend complementary studies with assessments in field and semi-field conditions, where on the one hand, the degradation and the small amount of insecticides that usually reach the pollen and/or nectar can mitigate potential harmful effects, but on the other hand, the need for foraging in more realistic environments may exacerbate the risk of insecticide exposure.